On Soft S_p-Closed and Soft S_p-Open Sets with Some Applications - Payman Majeed Mahmood; Halgwrd M. Darwesh; Hardi A. Shareef (Tikrit Journal of Pure Science)
In this article, the concept of a soft -closed set is introduced. Its relationships with some other types of soft sets are explored and discussed. In addition, via soft -closed sets and soft -open sets, the concepts soft -neighborhood, soft -limit point, soft -derived, soft -interior, soft -closure, and soft -boundary are introduced and investigated.